For Evaluation the Performances of Stochastic Streamflow Models for the Multi Reservoirs : Synthetic Streamflow Generation for Reservoir Management - Tukiman, Nurul Nadrah Aqilah; Harun, Sobri (International Journal of Integrated Engineering, 2021)
Pedu-Muda reservoirs responsible to supply sufficient water capacity during paddy cultivation period twice a year. Thus, improper management and operation of the reservoirs creating the scarcity issue of water availability especially during dry season. Synthetic streamflow being as a main role in predicting the capability and sustainability of these reservoirs to cope the demand. This study evaluated the performances of stochastic streamflow model to produce the synthetic streamflow generation. There were two comparable models; Valencia Schaake (VS) and Thomas Fiering (TF) which represented in disaggregation and aggregation models, respectively. The basis of the statistical characteristics consist of lag one correlation, mean, mean absolute error (MAE), and standard deviation (St.D) of annual and monthly levels for both models were compared to identify the model performances. The results revealed the generated streamflow series produced by VS models had better performances to the historical streamflow record than the TF model in term of annual and monthly. However, both models can preserve a good agreement to the mean even the range of monthly streamflow were overestimated/underestimated by VS and TF models respectively.